Exploratory factor analysis of the items for measuring consumers' online health information seeking - Engku Alwi, Sharifah Sumayyah; Azmi Murad, Masrah Azrifah; Abdullah, Salfarina; Kamaruddin, Azrina (Malaysian Public Health Physicians' Association, 2023)
With the phenomenal development and advancement of technology, coupled with the current concerns about effective consumer engagement in health information-seeking (HIS), e-health systems in healthcare are gaining the attention of more and more people. Past literature reviews on HIS show limited discussion on the dimensions that motivate HIS among consumers. This study’s main objective is to comprehensively validate twelve (12) dimensions of consumer online HIS using the Exploratory Factor Analysis (EFA) procedure. A cross-sectional research design was implemented to establish reliable measures in the online HIS construct. The questionnaire items were modified from 16 studies and adapted for this study. Consumers were selected based on simple random sampling from hospitals and universities in Kuala Lumpur and Selangor. Within three weeks, 120 participants completed the questionnaire. Initially, 76 items were formed to assess the online HIS construct. After conducting the EFA procedure, 13 items with a factor loading below the cut-off point of 0.60 were deleted, and 63 items with a factor loading above the cut-off point of 0.60 were retained and considered suitable for measuring the construct. This study has established the development of a reliable and valid instrument to assess the quality of the consumer online HIS construct.